Preventing Addiction Related Suicide: A Pilot Study - Voss, William D. (2013)
Persons addicted to alcohol and drugs are at 5–10 times higher risk for suicide as compared to the general population. To address the need for improved suicide prevention strategies in this population, the Preventing Addiction Related Suicide (PARS) module was developed. Pilot testing of 78 patients demonstrated significant post-treatment changes in knowledge (t (66) = 12.07, p= .000) and attitudes (t (75) = 6.82, p = .000) toward suicide prevention issues. Significant gains were maintained at one-month follow-up for changes in knowledge (t (55) = 6.33, p= .000) and attitudes (t (61) = 3.37, p= .0001), with changes in positive help seeking behaviors in dealing with suicidal issues in friends (χ(2) (1) =10.49, p = .007), family (χ(2) (1) = 9.81, p = .015), and self (χ(2) (1) = 19.62, p= .008) also observed. The PARS was also highly rated by treatment staff as feasible within their standard clinical practice.